Insights into projected changes in marine heatwaves from a high-resolution ocean circulation model - Hakase Hayashida (Nature Portfolio, 2020)
Marine heatwaves are likely to intensify in a warmer world, but prediction of these events is hampered by course-scale modeling. Here the authors develop a fine scale, global model which shows that marine heatwaves will amplify with greater spatial variability, particularly at western boundary regions.